(untitled) (Journal of the College of Basic Education, 2023)
The research focused on studying the geomorphological indicators affecting the slopes of Chainara Mountain that is located in the northern part of Iraq within the High Folds Belt, using geographic information systems technology and relying on the field study, with the aim of determining the level of probability of landslides over the slopes of Chinara, by conducting approved mathematical modeling of geomorphological indicators. A map of the potential for landslide hazards in the region was produced and classified into five levels. It was found that areas with moderate risk of landslides constitute the largest percentage, amounting to (32.1%) with an area of (92 km²), followed by low risk areas with a rate of (24.0%) with an area of (69 km²), High-risk areas, with a rate of (22.3%), with an area of (64 km²), and very high-risk areas, with a rate of (12.5%), with an area of (36 km²) out of the total area of the region amounting to (287 km²).